A Comparison of Robotic Versus Open Thyroidectomy for Papillary Thyroid Cancer. Issue 3 (June 2018) - Paek, Se Hyun; Kang, Kyung Ho; Park, Sung Jun
Abstract : Objectives: This study investigated the potential advantages of robotic thyroidectomy and determined whether it is safe and complete compared with conventional open surgery in patients with papillary thyroid cancer. Materials and Methods: A total 376 consecutive patients who underwent total thyroidectomy and central neck dissection for papillary thyroid cancer from February 2013 to July 2014 were retrospectively reviewed. Postoperative complication rates and surgical completeness were compared between the robotic and open groups. Results: Transient hypoparathyroidism was higher in the open group (10.5%) compared with the robotic group (2.8%; P =0.042). There were no differences in mean number of retrieved or metastatic lymph nodes. The mean values of stimulated thyroglobulin level were acceptably low in both groups. There was no difference in the proportion of patients with stimulated thyroglobulin levels <1 ng/mL. Conclusion: Our study results show that outcomes of robotic thyroidectomy may be similar to that of conventional thyroidectomy, with possible better preservation of the parathyroid blood supply.